Advanced Quadratic drag - How to solve?

So I have gotten this far...

a=((F_a-(c_d*rho_h*A*v^2)/2)-m_t*g_r)a=((FacdρhAv22)mtgr)

This is based upon F_a-(F_d+F_g)/m =aFaFd+Fgm=a

But aa is (dv)/(dt)dvdt

So this becomes a differential equation because the faster you go the harder it is to go faster.

How can one solve this?

Please note I'm currently a Calc AB student.

1 Answer
Jun 7, 2016

Supposing that
c_0 = F_a-m_t g_r = C^{te}c0=Famtgr=Cte
c_2=(c_d rho_h A)/2 = C^{te}c2=cdρhA2=Cte
we have v(t) = sqrt[c_0/c_2] Tanh(sqrt[c_0c_2] ( t+t_0))v(t)=c0c2tanh(c0c2(t+t0)) with t_0t0 integration constant

Explanation:

This equation

dot v(t) = c_0(t) + c_1(t)v(t) + c_2(t)v(t)^2.v(t)=c0(t)+c1(t)v(t)+c2(t)v(t)2

with V = c_2(t)vV=c2(t)v, S(t) = c_0(t)c_2(t)S(t)=c0(t)c2(t) and R(t) = c_1(t)+(dot c_2(t))/(c_2(t))R(t)=c1(t)+.c2(t)c2(t)

can be reduced to

dot V = V^2+R(t)V+S(t).V=V2+R(t)V+S(t)

which is the known Riccati equation.
https://en.wikipedia.org/wiki/Riccati_equation

Now making V = -(dot u)/uV=.uu the Riccati equation can be reduced to
a second order ODE which is

ddot u -R(t) dot u + S(t) u = 0

A solution u to this equation can be used to find the solution to the original equation

v = -(dot u)/(c_2(t)u)

As an example, supposing that

c_0 = F_a-m_t g_r = C^{te}
c_2=(c_d rho_h A)/2 = C^{te}

we obtain

v(t) = sqrt[c_0/c_2] Tanh(sqrt[c_0c_2] (t + t_0))

after solving

ddot u-c_0c_2 u = 0

with general solution

u(t) = C_1e^{sqrt(c_0c_2)t}+C_2e^{-sqrt(c_0c_2)t}

Explanation . substituting in

v(t) = -(dot u(t))/(c_2(t)u(t))

we get

v(t) = (sqrt[c_0 c_2] C_2 e^(-sqrt[c_0 c_2] t) - C_1 sqrt[c_0 c_2] e^( sqrt[c_0 c_2] t))/(c_2 (C_2 e^(-sqrt[c_0 c_2] t) + C_1 e^(sqrt[c_0 c_2] t)))

grouping

v(t) = sqrt(c_0c_2)/c_2((C_2 e^(-sqrt[c_0 c_2] t) - C_1e^(sqrt[c_0 c_2] t))/ (C_2 e^(-sqrt[c_0 c_2] t) + C_1 e^(sqrt[c_0 c_2] t)))

or

v(t) = sqrt(c_0c_2)/c_2((C_2 e^(-sqrt[c_0 c_2] t) - C_1e^(sqrt[c_0 c_2] t))/ (C_2 e^(-sqrt[c_0 c_2] t) + C_1 e^(sqrt[c_0 c_2] t)))

but

(C_2 e^(-sqrt[c_0 c_2] t) - C_1e^(sqrt[c_0 c_2] t))/ (C_2 e^(-sqrt[c_0 c_2] t) + C_1 e^(sqrt[c_0 c_2] t))=(e^(-sqrt[c_0 c_2] t) - C_1/C_2e^(sqrt[c_0 c_2] t))/ (e^(-sqrt[c_0 c_2] t) + C_1/C_2 e^(sqrt[c_0 c_2] t))

and EE a | abs(C_1/C_2) = e^{2a} then

(C_2 e^(-sqrt[c_0 c_2] t) - C_1e^(sqrt[c_0 c_2] t))/ (C_2 e^(-sqrt[c_0 c_2] t) + C_1 e^(sqrt[c_0 c_2] t))=(e^(-sqrt[c_0 c_2] t-a) - e^(sqrt[c_0 c_2] t+a))/ (e^(-sqrt[c_0 c_2] t-a) + e^(sqrt[c_0 c_2] t+a)) = sinh(sqrt(c_0c_2t+a))/cosh(sqrt(c_0c_2t+a)) = tanh(sqrt(c_0c_2t+a))

Finally putting all together

v(t) = sqrt[c_0/c_2]Tanh(sqrt[c_0c_2] t + a) or

v(t) = sqrt[c_0/c_2] Tanh(sqrt[c_0c_2] (t + t_0))

with a = t_0 sqrt(c_0c_2)